A case of marked bilateral asymmetry in the sacral alae of the Neandertal specimen Regourdou 1 (Périgord, France). Issue 2 (11th November 2019) - Rmoutilová, Rebeka; Gómez‐Olivencia, Asier; Brůžek, Jaroslav; Holliday, Trenton; Ledevin, Ronan; Couture‐Veschambre, Christine; Madelaine, Stéphane; Džupa, Valér; Velemínská, Jana; Maureille, Bruno
Abstract: Objectives: A marked asymmetry was previously reported in the sacral alae and S1‐L5 facets orientation of the Neandertal individual Regourdou 1. Here, we provide a detailed description and quantification of the morphology and degree of asymmetry of this sacrum. Material and methods: Regourdou 1 was compared to a modern human sample composed of 24 females and 17 males, and to other Neandertal individuals. Both traditional and geometric morphometric analyses were used in order to quantify the degree of sacral asymmetry of Regourdou 1. Results: The asymmetry of both sacral alae and facets orientation substantially exceeds directional and absolute asymmetry of the healthy modern sample. Regourdou 1 shows a considerably shorter right ala, which is absolutely and relatively outside of the modern and Neandertal variations. Conclusion: Regourdou 1 shows marked sacral asymmetry that probably originated in early ontogenetic development. An asymmetric sacrum reflects asymmetric load dissipation and could relate to other morphological abnormalities observed in the skeleton, especially the mild scoliosis of the spine and the asymmetry of the femoral diaphyses. Further investigation is necessary to elucidate the relationship between those morphologies as well as a potential impact on the life of the individual.